(untitled) (Journal of Human Sciences, 2022)
There are many opinions among researchers about the semantic purpose of this diversity, and each carries a point of view from scientific premises, but the researchers have embarked on research on this subject from the premise that this phenomenon, with its diversity, must be unique in semantic secrets in the Qur’anic text, because the Qur’an text was not Just a container for the uses of the Arabs only, but he made all linguistic phenomena in a special way that serves the language of the Qur’an. In our study, we were exposed to this linguistic phenomenon known in the language of the Arabs, and we reached many results, foremost of which is the singling out of the language of the Qur’an with special connotations, these indications were sensed by the commentators during their interpretation of the verses.